Exercise Motivation among Fitness Center Members: A Combined Qualitative and Q-Sorting Approach - Nam, Truong Thanh; Suwanbamrung, Charuai; Dadras, Omid; Hou, Xiang-Yu; Phu, Doan Hoang; Tin, Pham Trung; Quang, Huynh Khai; Thuy, Thai Thi Ngoc; Ageru, Temesgen A.; Aekwarankoon, Saifon; Isaramalai, Sang-arun; Le, Cua Ngoc (Journal of Human, Earth, and Future, 2023)
This study aimed to explore the components of Exercise Maintenance Motivation (EMM) and identify its consensus and distinguishing aspects among members of fitness centers (FCs) in Vietnam. The study incorporated both qualitative and Q-sorting methodologies across two stages. The first stage involved conducting ten in-depth and four focus-group interviews with 39 members of six different FCs in Vietnam, resulting in the generation of 40 EMM statements. In the second stage, these statements were subjected to Q-sorting by 39 participants. The KADE application for the Q method was used for data analysis, and Principal Component Analysis was employed to determine the optimal number of factors. The analysis yielded four factors, encompassing 34 statements and accounting for 86% of the variance in EMM components among participants. These components, labeled "F1. Exercise achievements”, "F2. Exercise environments”, "F3. Exercise enjoyment”, and "F4. Workout-aholic”, achieved consensus among 17 (37%), 14 (30%), 5 (12%), and 3 (7%) participants, respectively. The leading motivational expressions were "get to be healthier”, "a better-looking appearance”, and "get a fit body appearance”. These were followed by FC-based supportive exercise conditions, positive feelings, and exercise addiction. There were five consensus statements that spanned all four factors. The numbers of distinguishing statements varied across factors, with F1, F3, and F4 each contributing 11 (28.2%) and F2 contributing 15 (38.5%). This study contributed to the four central drivers of EMM. To facilitate the development of a comprehensive EMM scale, future research should incorporate larger samples, allowing for a dissection of motivational paradigms. Doi: 10.28991/HEF-2023-04-03-07 Full Text: PDF